2001
DOI: 10.1038/sj.onc.1204721
|View full text |Cite
|
Sign up to set email alerts
|

Defects in transcription coupled repair interfere with expression of p90MDM2 in response to ultraviolet light

Abstract: Ultraviolet (UV) irradiation transiently stabilizes p53 through a mechanism that may require a decrease in the activity of the ubiquitin ligase, p90 MDM2 . Conversely, the recovery of low levels of p53 following UV exposure may depend on an increase in p90 MDM2 . The level of p90 MDM2 is increased by UV light following the p53-dependent induction of an internal mdm2 promoter, P2. If this induction of mdm2 were critical for the recovery of low levels of p53 following UV exposure, defects in mdm2's transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Mdm2 also fails to accumulate post-UV in CS-A and XP-A cells, implying that this response is related to an inability to carry out TC-NER. 18,26 However, as shown here, not all TC-NER defective cells respond to UV irradiation in the same way. MDM2 transcripts, particularly those from the P2 promoter, fail to accumulate in XPG-deficient cells post-UV treatment whereas they do accumulate, albeit later than normal, in CS-A and CS-B cells (Figure 6).…”
Section: P53 and Mdm2 Changes In Xpg-deficient Fibroblastsmentioning
confidence: 50%
See 1 more Smart Citation
“…Mdm2 also fails to accumulate post-UV in CS-A and XP-A cells, implying that this response is related to an inability to carry out TC-NER. 18,26 However, as shown here, not all TC-NER defective cells respond to UV irradiation in the same way. MDM2 transcripts, particularly those from the P2 promoter, fail to accumulate in XPG-deficient cells post-UV treatment whereas they do accumulate, albeit later than normal, in CS-A and CS-B cells (Figure 6).…”
Section: P53 and Mdm2 Changes In Xpg-deficient Fibroblastsmentioning
confidence: 50%
“…25,26 To determine the potential effect of transcriptional regulation on Mdm2 protein accumulation, we examined by quantitative real-time PCR the steady-state levels of the P1 and P2 transcripts at various times post-UV, using the primers and exon junction TaqMan probes indicated in Figure 6a.…”
Section: Mdm2 Transcripts Are Made In Reduced Amounts In Tc-ner Defecmentioning
confidence: 99%
“…Our MDM2 mRNA analysis does not discriminate between transcripts from two MDM2 promoters, reflecting p53-independent and p53-responsive mRNA accumulation, respectively (11). However, in contrast to transcripts from the human gene, both promoter transcripts from the mouse gene can be induced by DNA-damaging agents and have been shown to support MDM2 protein accumulation (37,38). It is thus possible that the increased MDM2 mRNA levels resulted in increased protein synthesis, but that a rapid turnover of MDM2 prevented increasing protein levels.…”
Section: Rt±pcr and Ishmentioning
confidence: 70%
“…Investigations of HCT-116 MLH1 -deficient cells have revealed hypersensitivity to UV light due to dysfunction of TC-NER, while artificially introduction of MLH1 gene to this cell line leads to TC-NER system activity and hence reduced sensitivity to UV light [54], [56]. It has also been reported that dysfunction of TC-NER system down-regulates transcription of particular genes [57]. These observations suggest that there may be a similar MLH1 mechanism of action on the regulation of FXN transcription.…”
Section: Discussionmentioning
confidence: 99%